Advances in stem cell therapy for diabetic foot - Xia, Yinfeng; Wu, Ping; Chen, Hong; Chen, Zhiyong (Frontiers in Genetics, 2024)
Diabetic Foot Ulcers (DFU) represent a grave complication often encountered in the advanced stages of diabetes mellitus. They frequently lead to recurrent hospitalizations and, in severe cases, can result in life-threatening conditions such as infections, gangrene, and even amputationDiabetic foot ulcers (DFU), as a serious complication in the late stage of diabetes mellitus, are prone to lead to repeated hospitalization, and in severe cases, infection, gangrene, and even amputation. Although there are many methods for treating diabetic foot, there is no clear and effective method to reduce the amputation rate of diabetic foot patients. In recent years, advancements in the understanding of stem cell therapy for the treatment of DFU have shed light on its potential as a novel therapeutic approach In recent years, as the research on stem cell therapy for diabetic foot is gradually deepening, stem cells are expected to become a new therapeutic method for treating DFU in the future. Their therapeutic effects are through promoting angiogenesis, secreting paracrine factors, controlling inflammation, promoting collagen deposition, and regulating immunity, etc. Despite numerous studies confirming the efficacy of stem cell therapy in treating DFU, there is still a need for the establishment of standardized treatment protocols. Although numerous studies have shown that stem cell therapy for DFU is real and effective, there has not yet been a standardized treatment protocol. This article reviews studies related to stem cell therapy for DFU, looking at the mechanism of action, types of stem cells, and modes of administration.